2012
DOI: 10.3892/mmr.2012.1191
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-27a inhibitors alone or in combination with perifosine suppress the growth of gastric cancer cells

Abstract: Abstract. is an oncogene that contributes to drug resistance in various types of cancer. However, the involvement of miR-27a in gastric cancer has yet to be elucidated. Perifosine is an alkylphospholipid exhibiting antitumor activity as shown in both preclinical studies and clinical trials. The effects of perifosine on gastric cancer have yet to be determined. Therefore, this study was conducted to detect the role of miR-27a and perifosine in human gastric cancer. miR-27a was found to be expressed in human ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 32 publications
(31 reference statements)
2
0
0
Order By: Relevance
“…Liu et al have elucidated that miR-27a was highly expressed in human MGC-803 GC cells [14], which is in accordance with our study. Besides, it was also supported by a report that a high expression of miR-27a was found in GC tissues in contrast with their matched non-tumor adjacent tissues [36]. Taken together, we have further demonstrated that miR-27a may act as an oncogene to be associated with carcinogenesis in human GC.…”
Section: Discussionsupporting
confidence: 88%
“…Liu et al have elucidated that miR-27a was highly expressed in human MGC-803 GC cells [14], which is in accordance with our study. Besides, it was also supported by a report that a high expression of miR-27a was found in GC tissues in contrast with their matched non-tumor adjacent tissues [36]. Taken together, we have further demonstrated that miR-27a may act as an oncogene to be associated with carcinogenesis in human GC.…”
Section: Discussionsupporting
confidence: 88%
“…Our result has demonstrated that miR27a level of Colon cancer group was much higher than that of Normal and Colitis groups (P<0.05). A recent study suggested that miR27a may have a high expression level in gastric cancer (Liu et al, 2013). This is similar with the result made in our paper.…”
Section: Discussionsupporting
confidence: 83%